Dampak Struktur Kepemilikan dan Karakteristik Dewan Direksi Terhadap Strategi Penghindaran Pajak - Susanto, Androni; Serly, Serly; Jasmine, Jasmine (Jurnal Pendidikan Ekonomi (JUPE), 2024)
The aim of the research is to determine the influence of ownership structure and characteristics of the board of directors on tax avoidance strategies in manufacturing sector companies listed on the BEI in 2018-2022. Tax avoidance calculations are represented by ETR and CFETR. Based on the criteria, there are 767 data observations for ETR and 717 data for CFETR. Comparative causal research is used to determine each relationship. Data is processed to formulate hypotheses using descriptive methods and regression methods. The research conclusion is that institutional ownership and board size have a negative effect and foreign ownership has a positive effect on tax avoidance. Meanwhile, managerial ownership, board independence and board meeting frequency have no influence on tax avoidance.